2022
DOI: 10.3390/rs14051251
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Above-Ground Biomass of Winter Wheat Based on Consumer-Grade Multi-Spectral UAV

Abstract: One of the problems of optical remote sensing of crop above-ground biomass (AGB) is that vegetation indices (VIs) often saturate from the middle to late growth stages. This study focuses on combining VIs acquired by a consumer-grade multiple-spectral UAV and machine learning regression techniques to (i) determine the optimal time window for AGB estimation of winter wheat and to (ii) determine the optimal combination of multi-spectral VIs and regression algorithms. UAV-based multi-spectral data and manually mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 114 publications
4
37
0
1
Order By: Relevance
“…Previous studies have shown that preprocessing of spectra can effectively eliminate noise and baseline drift and highlight the location of spectral feature bands (Arneberg et al, 2007). The accuracy of the models built using relevant studies (Nguyen and Lee, 2006;Li et al, 2016;Wang et al, 2020;Li et al, 2020b) using different forms of spectral transformations is higher than the models built using the original spectra. Feature screening mainly solves the collinearity problem of the spectrum, and wavelengths with less redundant information are selected for direct model construction, which is a simple, fast, and intuitive method easy to implement (Bai et al, 2018;Jia et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that preprocessing of spectra can effectively eliminate noise and baseline drift and highlight the location of spectral feature bands (Arneberg et al, 2007). The accuracy of the models built using relevant studies (Nguyen and Lee, 2006;Li et al, 2016;Wang et al, 2020;Li et al, 2020b) using different forms of spectral transformations is higher than the models built using the original spectra. Feature screening mainly solves the collinearity problem of the spectrum, and wavelengths with less redundant information are selected for direct model construction, which is a simple, fast, and intuitive method easy to implement (Bai et al, 2018;Jia et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…The multiple types of VIs can make more extensive use of waveband information and provide more complementary predictors for the NC model construction. Thus, the machine learning algorithms have the ability to integrate and utilize the spectral information contained in VIs, which could be the explanation for the great performance achieved for the combined use of VIs (Wang et al, 2022a). However, probably due to the contrasting correlation patterns observed here - VIs and TF were correlated positively and negatively with NC respectively, the combined use of both types of variables did not improve the predictions of NC.…”
Section: Discussionmentioning
confidence: 99%
“…The spectral resolution of the monochromatic sensors includes: a blue band with 450 nm center and 16 nm bandwidth, a green band with 560 nm center and 16 nm bandwidth, a red band with 650 nm center and 16 nm bandwidth, a red-edge band with 730 nm and 16 nm bandwidth and a near-infrared band with 840 nm and 26 nm bandwidth. More specific parameters of the UAV and the camera are demonstrated in (Wang et al, 2022a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…How to disentangle the individual contribution of the LAI and suppress the LCC signals in canopy reflectance is thus essential and indispensable for LAI estimation. Besides, spectral saturation issue often happens in the dense vegetated JSTARS-2022-01606 condition [15,16], and this further weaken the LAI estimating accuracy in large LAIs.…”
Section: Introductionmentioning
confidence: 99%